The surface geometries of the medium and high coverage carbon monoxide structures c(2 × 4)-(2CO) and p(√7 × √7)R19°-(4CO) on Ni1 1 1 - Braun, Wolfgang; Steinrück, Hans-Peter; Held, Georg (Surface Science, 2005)
The surface geometries of the p(7×7)R19°-(4CO) and c(2 × 4)-(2CO) layers on Ni1 1 1 and the clean Ni1 1 1 surface were determined by low energy electron diffraction structure analysis. For the clean surface small but significant contractions of d and d (both 2.02 Å) were found with respect to the bulk interlayer distance (2.03 Å). In the c(2 × 4)-(2CO) structure these distances are expanded, with values of d = 2.08 Å and d = 2.06 Å and buckling of 0.08 and 0.02 Å, respectively, in the first and second layer. CO resides near hcp and fcc hollow sites with relatively large lateral shifts away from the ideal positions leading to unequal C-Ni bond lengths between 1.76 and 1.99 Å. For the p(7×7)R19°-(4CO) layer two best fit geometries were found, which agree in most of their atomic positions, except for one out of four CO molecules, which is either near atop or between bridge and atop. The remaining three molecules reside near hcp and fcc sites, again with large lateral deviations from their ideal positions. The average C-Ni bond length for these molecules is, however, the same as for CO on hollow sites at low coverage. The average C-Ni bond length at hollow sites, the interlayer distances, and buckling in the first Ni layer are similar to the c(2 × 4)-(2CO) geometry, only the buckling in the second layer (0.08 Å) is significantly larger. Lateral and vertical shifts of the Ni atoms in the first layer lead to unsymmetric environments for the CO molecules, which can be regarded as an imprint of the chiral p(7×7)R19° lattice geometry onto the substrate. © 2004 Elsevier B.V. All rights reserved.
Keywords: nickel; carbon monoxide; low energy electron diffraction (LEED)